Airport pricing and regulation under passenger demand uncertainty. Issue 1 (31st December 2022) - Liu, Wen-Jing; Gong, Xu; Li, Zhi-Chun
Abstract : This paper addresses the airport pricing and regulation issues in the presence of passenger demand uncertainty. The regulatory schemes concerned include the single-till and dual-till price-cap regulations. A vertical-structure model is presented to determine the optimal airport charges under the single-till and dual-till price-cap regulations. The effects of the airport regulatory level and the risk-averse preferences of stakeholders in the system on airport pricing are also examined. The results show that at a high passenger demand uncertainty level, the dual-till regulation would outperform the single-till regulation in terms of social welfare. However, at a low passenger demand uncertainty level, which regulation is better depends on various factors, such as the regulatory level and risk-averse preference.